International project management for technical professionals - Porter, Brian E., 1976- (ASME Press, 2020)
"This book has been intended to help other learn from my experiences as a project manager around the world. My travels have taken me to remote villages in Tanzania, major manufacturing in China and business hubs in the United Arab Emirates. The variety of experiences have shaped who I am and hopefully you will gain from them as well. In fact, one of my most frequent quotes is "smart people learn from their mistakes; wise people learn from others' mistakes". Hopefully you can learn from both the successes and failures noted"--